Determination of the geographical origin of Brazilian wines by isotope and mineral analysis - Dutra, S. V.; Adami, L.; Marcon, A. R.; Carnieli, G. J.; Roani, C. A.; Spinelli, F. R.; Leonardelli, S.; Ducatti, C. [UNESP]; Moreira, M. Z.; Vanderlinde, R. (Springer Heidelberg, 2011)
In the present research, we studied wines from three different south Brazilian winemaking regions with the purpose of differentiating them by geographical origin of the grapes. Brazil's wide territory and climate diversity allow grape cultivation and winemaking in many regions of different and unique characteristics. The wine grape cultivation for winemaking concentrates in the South Region, mainly in the Serra GaA(0)cha, the mountain area of the state of Rio Grande do Sul, which is responsible for 90% of the domestic wine production. However, in recent years, two new production regions have developed: the Campanha, the plains to the south and the Serra do Sudeste, the hills to the southeast of the state. Analysis of isotopic ratios of (18)O/(16)O of wine water, (13)C/(12)C of ethanol, and of minerals were used to characterize wines from different regions. The isotope analysis of delta(18)O of wine water and minerals Mg and Rb were the most efficient to differentiate the regions. By using isotope and mineral analysis, and discrimination analysis, it was possible to classify the wines from south Brazil.
Keywords: Wine; Stable isotopes; Minerals; Geographical origin